2015
DOI: 10.1093/femsec/fiv084
|View full text |Cite
|
Sign up to set email alerts
|

Complex coupled metabolic and prokaryotic community responses to increasing temperatures in anaerobic marine sediments: critical temperatures and substrate changes

Abstract: The impact of temperature (0–80°C) on anaerobic biogeochemical processes and prokaryotic communities in marine sediments (tidal flat) was investigated in slurries for up to 100 days. Temperature had a non-linear effect on biogeochemistry and prokaryotes with rapid changes over small temperature intervals. Some activities (e.g. methanogenesis) had multiple ‘windows’ within a large temperature range (∼10 to 80°C). Others, including acetate oxidation, had maximum activities within a temperature zone, which varied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 91 publications
3
18
0
Order By: Relevance
“…It is likely that organisms with a high degree of physiological flexibility in the slow warming rate may be able to buffer their functioning (i.e., resilient or resistant) against a gradual increase in temperature (Holling, 1973) If physiological acclimation of individual taxa is not possible under a rapid warming event, then marginal microbial taxa may become more successful, and the final configuration of the community would depend on the ability of populations to withstand and adapt to an environmental perturbation (i.e., temperature; Allison & Martiny, 2008;Matulich & Martiny, 2015). Within this context, the presence of isotopically lighter CH 4 (and isotopically heavier CO 2 ) in both step and ramp treatments than in the control (Table 2) were in general agreement with previous findings of shifting from acetotrophic dominated to hydrogenotrophic dominated methanogenic pathway with warming (Conrad, Klose, & Noll, 2009;Fu, Song, & Lu, 2015 Relatively greater availability of labile C substrates (e.g., microbial necromass) could stimulate the activity of heterotrophic acetogens, and selectively favor acetotrophic methanogenesis in the step warming treatment (Blake, Tveit, Øvre as, Head, & Gray, 2015;Nozhevnikova et al, 2007;Roussel et al, 2015). Following the same logic, slow depolymerization of resources per unit time in the ramp treatment may restrict instantaneous availability of labile C substrate and trigger autotrophic methanogenic (i.e., H 2 /CO 2 reduction) pathway either by promoting reductive assimilation of CO 2 (Xia et al, 2009) or by enhancing hydrogen fermentation (Bisaillon, Turcot, & e270 | Hallenbeck, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…It is likely that organisms with a high degree of physiological flexibility in the slow warming rate may be able to buffer their functioning (i.e., resilient or resistant) against a gradual increase in temperature (Holling, 1973) If physiological acclimation of individual taxa is not possible under a rapid warming event, then marginal microbial taxa may become more successful, and the final configuration of the community would depend on the ability of populations to withstand and adapt to an environmental perturbation (i.e., temperature; Allison & Martiny, 2008;Matulich & Martiny, 2015). Within this context, the presence of isotopically lighter CH 4 (and isotopically heavier CO 2 ) in both step and ramp treatments than in the control (Table 2) were in general agreement with previous findings of shifting from acetotrophic dominated to hydrogenotrophic dominated methanogenic pathway with warming (Conrad, Klose, & Noll, 2009;Fu, Song, & Lu, 2015 Relatively greater availability of labile C substrates (e.g., microbial necromass) could stimulate the activity of heterotrophic acetogens, and selectively favor acetotrophic methanogenesis in the step warming treatment (Blake, Tveit, Øvre as, Head, & Gray, 2015;Nozhevnikova et al, 2007;Roussel et al, 2015). Following the same logic, slow depolymerization of resources per unit time in the ramp treatment may restrict instantaneous availability of labile C substrate and trigger autotrophic methanogenic (i.e., H 2 /CO 2 reduction) pathway either by promoting reductive assimilation of CO 2 (Xia et al, 2009) or by enhancing hydrogen fermentation (Bisaillon, Turcot, & e270 | Hallenbeck, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…Our understanding of the ecology and lifestyles of SRM beyond the SMTZ and in the deep biosphere is even more limited. Sulfate depletion, decreasing nutrient availability and increasing pressure and temperature are general environmental factors that constrain the assembly of SRM communities in deeper sediment layers (Glombitza et al ., ; Roussel et al ., ). Biogeochemical data suggests the existence of high‐affinity SRM that are especially adapted to low sulfate concentrations in marine sediments (Tarpgaard et al ., ).…”
Section: Dissimilatory Sulfate Reductionmentioning
confidence: 97%
“…Head et al, 2003;Hoehler and Jørgensen, 2013;Lever et al, 2015); the potential supply of metabolic energy is low in sedimentary settings that tend to be lean in electron acceptors and/or donors compared to hydrothermal vents, at which reduced fluids are mixed with oxygenated seawater. Experimental studies with surface sediment demonstrated a nonlinear effect of temperature on biogeochemistry and prokaryotes, with rapid changes occurring over small temperature intervals, and revealed that substrate addition and increase of metabolic energy result in stimulation of microbial activities at elevated temperatures (Roussel et al, 2015). The influence of temperature on microbial communities was one of the central questions during Integrated Ocean Drilling Program Expedition 331 at the Iheya North hydrothermal field in the Okinawa Trough, but this task was severely complicated by extremely high geothermal gradients.…”
Section: Introductionmentioning
confidence: 99%